Fluorescent nanosphere transport: groundwater tracing and implications for nanoparticle migration through groundwater systems - King, Charlene N., author; Sanford, William E., advisor; Li, Yan Vivian, advisor; Ronayne, Michael J., committee member; Sale, Thomas, committee member (Colorado State University. Libraries, 2015)
Engineered nanoparticles (NPs) are being introduced to water supplies and many NPs have been shown to have deleterious effects on plants and animals; however, their behavior in natural substrates is not well characterized. In an effort to characterize nanoparticle migration through porous media a dual-tracer of fluorescent carbon nanospheres (CNP) and bromide (Br) were deployed through columns of porous media designed to be homogeneous, have dual-porosity, or be reactive. The CNP are hydrophilic, non-toxic, inert, and only 5 to 10 nm in diameter. Unlike other colloid tracers CNP are designed to be inexpensive, easy to identify, and not susceptible to pore throat filtering or settling making them an ideal particle tracer. The results of the homogeneous tests show that CNP and Br had identical breakthrough curves with retardation factors close to 1, confirming that CNP transport conservatively through silica sand. The results of the dual-porosity tests suggested that CNP may undergo slightly less transverse diffusion (mass transfer) into the immobile zone than the solute tracer Br. However the differences were less than expected because molecular diffusion was overwhelmed by the high pore velocities in the experiments. The results of the reactive media tests showed that in columns with surface-modified zeolite (SMZ) the CNP transported conservatively, while Br had a retardation factor 11 to 18 times higher, due to sorption. This means that the CNP can function as the conservative species used in a multiple tracer test to quantify the surface area exposure of other minerals or contaminants with a surface charge along preferential flow paths. During each of these experiments the average mass recovery for CNP was 95% indicating that there was minimal mass loss from pore throat filtering, settling, or sorption. Not only are CNP an extremely useful new tracer for groundwater systems, but they also provide insight as to how other NPs might be transported once introduced into the subsurface. NPs with surfaces that have been functionalized to be hydrophobic or preferentially sorb to a target constituent behave differently. If NPs which sorb to a particular contaminant are introduced to the subsurface it could facilitate transport of that contaminant or facilitate sorption. Similarly the rapid transport properties of hydrophilic NPs should be considered where any toxic NP is being introduced to natural systems.